Case Report: Co-infection with cat-scratch disease and infectious mononucleosis: a rare clinical entity - Huang, Wenting; Yuan, Jingping; He, Huihua (Frontiers in Pediatrics, 2025)
BackgroundCat-scratch disease (CSD) and infectious mononucleosis (IM) are prevalent infections in children and adolescents. However, the concurrent occurence of these two diseases remains a rare clinical entity. We reported a 13-year-old male who presented with unilateral inguinal lymphadenopathy and fever, and had a history of cat scratch. Based on histopathological findings, special stains, and immunohistochemical analysis, the patient was diagnosed with both CSD and IM.Case presentationA 13-year-old male presented with a palpable mass on the left thigh and fever. Radiological findings suggested a diagnosis of reactive lymphadenopathy. Laboratory tests revealed elevated C-reactive protein (CRP) levels and the presence of Gram-negative bacilli. Given these findings, the patient underwent an excisional biopsy of the lymph node. Histopathological examination of the excised lymph node revealed features of reactive lymphadenopathy, characterized by mild follicular hyperplasia and an increased number of mononuclear cells in the periphery. Notably, the lymph node displayed multiple small granular microabscesses located centrally and surrounded by a mantle of histiocytes and neutrophils. Special staining with Warthin-Starry silver stain revealed numerous bacilli within the abscesses, findings consistent with Bartonella henselae infection. Furthermore, immunohistochemical analysis showed CD20-positive B cells in the follicular areas and CD30-positive plasmablasts and plasma cells. Epstein–Barr virus (EBV) in situ hybridization for Epstein–Barr encoded RNA (EBER) was positive in the B-cell lineage, confirming EBV infection. The lymph node showed a polyclonal B-cell proliferation, encompassing a mature B-cell lineage with plasmablasts and plasma cells, indicating a reactive process rather than malignancy.ConclusionThis case represents the first reported instance of a pediatric patient diagnosed with concurrent CSD and IM by pathological examination. The diagnosis was based on histopathological features, special stains, and immunohistochemical findings. The coexistence of these two distinct infections highlights the importance of considering multiple etiologies when evaluating reactive lymphadenopathy.